The favourable prognostic value of oestrogen receptor β immunohistochemical expression in breast cancer. Issue 5 (27th April 2004) - Nakopoulou, L; Lazaris, A C; Panayotopoulou, E G; Giannopoulou, I; Givalos, N; Markaki, S; Keramopoulos, A
Abstract : Aims: Oestrogen receptor β (ERβ) is present in breast tumours, although its prognostic and pathophysiological roles remain to be established. Methods: Standard immunohistochemistry with a specific monoclonal antibody was performed on paraffin wax embedded sections; 10% of strongly immunostained carcinoma cells was used as the cutoff point to classify tumours as ERβ positive. Statistical correlations were sought with clinicopathological variables (including hormone receptor status) and disease free (DFS) and overall survival (OS) in a well documented series of 181 invasive breast carcinomas. Cell proliferation was assessed immunohistochemically by topoisomerase IIa (TopoIIa) index; p53 protein accumulation and c-erbB-2 oncoprotein expression were also taken into account. Results: ERβ immunoreactivity was detected in most specimens (71.2%); it was positively linked to ERα immunoreactivity and increased TopoIIα index, and inversely to c-erbB-2 overexpression. There were no correlations with p53 immunostaining or other clinicopathological parameters. A significant favourable impact of ERβ immunopositivity emerged with regard to DFS and OS in both univariate and multivariate analysis; ERβ immunopositivity retained its favourable significance with regard to DFS in the subgroups of stage I and II patients when they were examined separately. Progesterone receptor expression also had an independent favourable influence on survival, albeit with less significance. In contrast, survival was not significantly influenced by ERα status. Conclusions: Because of the positive association between ERβ immunoreactivity and TopoIIα expression, the presence of ERβ in breast cancer cells could be considered an indication of increased proliferation. Nevertheless, ERβ immunoreactivity emerges as a valuable, independent indicator of favourable prognosis.